Effects of Annealing on Hydrogen Storage Performance in TiZrCrMnFeNi High-Entropy Alloy - Tengfei Cheng; Jing Huang; Wanggang Fang; Liqing He; Xiangqun Duan; Guotong Zou; Xiao Li; Xinghai Ren (Crystals)
This study employed annealing heat treatment ranging from 900 to 1300 °C to systematically investigate the effects of annealing temperature on the microstructure and hydrogen storage performance of the equimolar TiZrCrMnFeNi high-entropy alloy. The research indicates that the TiZrCrMnFeNi high-entropy alloy is composed of the C14 Laves phase and a small amount of cubic phase. Compared to the as-cast alloy, the alloy annealed at high temperature (1000~1200 °C) exhibited increased microstructure homogeneity, a higher content of the C14 Laves phase, and a significant enhancement in hydrogen storage capacity. The annealing heat treatment led to changes in the unit cell volume of the C14 Laves phase, with an inverse relationship between unit cell volume and hydrogen absorption and desorption plateau pressures. An increase in unit cell volume resulted in a lower desorption plateau pressure, making the desorption reaction more difficult and consequently increasing the enthalpy change for desorption. This study not only reveals the intrinsic relationship between annealing temperature and the hydrogen storage performance of high-entropy alloys, but also provides significant experimental evidence and theoretical guidance for the design and development of high-entropy alloy materials with excellent hydrogen storage characteristics.